The Value of Preoperative Exercise and Education for Patients Undergoing Total Hip and Knee Arthroplasty: A Systematic Review and Meta-Analysis. Issue 12 (December 2017) - Moyer, Rebecca; Ikert, Kathy; Long, Kristin; Marsh, Jacquelyn
Abstract : Background: Existing evidence regarding the value of preoperative education and/or exercise (prehabilitation) for patients undergoing total joint replacement is conflicting. The purpose of this study was to conduct an updated, comprehensive systematic review with meta-analyses to determine the longitudinal effects and efficacy of prehabilitation on postoperative outcomes in patients undergoing total hip arthroplasty (THA) or total knee arthroplasty (TKA). Methods: We searched 11 electronic databases (MEDLINE, AMED, CINAHL, Embase, Scopus, ProQuest, PEDro, SportDiscus, PsycINFO, and Cochrane) from their inception to May 2016 for randomized controlled trials that compared changes in pain, function, strength, anxiety, and hospital length of stay following THA or TKA. Two reviewers independently determined study eligibility, rated study quality, and extracted data. There were no restrictions on study dates, patient characteristics, or the follow-up time point at which postoperative outcomes were measured. We excluded trials comparing 2 interventions. Methodological quality assessments were performed using the Cochrane risk-of-bias tool. We calculated pooled estimates, with 95% confidence intervals (CIs), of standardized mean differences (SMDs). Results: Thirty-five studies with 2, 956 patients were included. After a preoperative program, patients undergoing THA, but not TKA, had significantly less postoperative pain than controls (SMD = 0.15, 95% CI = 0.03 to 0.27, p = 0.017). Postoperative function was also significantly improved compared with controls, with similar improvement after THA (SMD = 0.32, 95% CI = 0.15 to 0.50, p < 0.001) and TKA (SMD = 0.32, 95% CI = 0.06 to 0.57, p = 0.015). Significantly greater quadriceps strength was observed after TKA (SMD = 0.42, 95% CI = 0.16 to 0.68, p = 0.002). No significant differences in hamstring strength were observed between groups after TKA (p = 0.132). Small-to-moderate but nonsignificant improvements in anxiety (SMD = 0.17, 95% CI = −0.05 to 0.39; p = 0.128) were observed after THA, and length of stay was significantly shorter after TKA (SMD = 0.54, 95% CI = 0.24 to 0.84, p < 0.001) and THA (p = 0.027). Conclusions: Overall effect sizes for prehabilitation were small to moderate. In patients undergoing TKA, significant improvements were observed in function, quadriceps strength, and length of stay. In patients undergoing THA, significant improvements were observed in pain, function, and length of stay. Included studies were inconsistent with regard to the types of outcome measures reported, and the quality of the interventions varied. A more standardized approach to reporting of clinical trial interventions and patient compliance is needed to thoroughly evaluate the effects of prehabilitation on postoperative outcomes. Level of Evidence: TherapeuticLevel II . See Instructions for Authors for a complete description of levels of evidence.